Bacteriophage control of Campylobacters in retail poultry - Atterbury, Robert J. (2004)
Food-borne disease continues to be a major cause of human morbidity and mortality. During the past few decades, Campylobacter jejuni has ascended to become the greatest cause of bacterial enteric disease worldwide. Anecdotal evidence suggests the majority of human campylobacteriosis in industrialised countries is caused by the consumption of undercooked chicken. Campylobacter continues to frustrate current control strategies throughout the food chain and in 2001 was responsible for over 56, 000 cases of food poisoning in the U.K. alone. The work presented in this thesis examined the potential of host-specific bacteriophage as a novel measure to control the population of Campylobacter in poultry production.